Cardiovascular Risk Reduction with Renin-Angiotensin Aldosterone System Blockade - Nancy Houston Miller (Hindawi Limited, 2010)
This paper examines the evidence supporting treatments within the renin-angiotensin aldosterone system (RAS), the role cardioprotection plays within the management of hypertension, considerations around medication adherence, and the role of the nurse or nurse practitioner in guiding patients to achieve higher hypertension control rates. A large body of data now exists to support the use of angiotensin receptor blockers (ARBs) and angiotensin-converting enzyme inhibitors (ACEIs) which act on RAS, in the management of hypertension and their effect on cardiovascular risk reduction. Current evidence suggests that inhibition of the RAS is an important target for cardioprotection. RAS inhibition controls blood pressure and also reduces target-organ damage. This is especially important in populations at high-risk for damage including patients with diabetes and those with chronic kidney disease. Both ARBs and ACEIs target the RAS offering important reductions in both BP and target organ damage.